2004
DOI: 10.1099/ijs.0.02840-0
|View full text |Cite
|
Sign up to set email alerts
|

Mesorhizobium septentrionale sp. nov. and Mesorhizobium temperatum sp. nov., isolated from Astragalus adsurgens growing in the northern regions of China

Abstract: Ninety-five rhizobial strains isolated from Astragalus adsurgens growing in the northern regions of China were classified into three main groups, candidate species I, II and III, based on a polyphasic approach. Comparative analysis of full-length 16S rRNA gene sequences of representative strains showed that candidate species I and II were Mesorhizobium, while candidate species III, which consisted of non-nodulating strains, was closely related to Agrobacterium tumefaciens. The phylogenetic relationships of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…STM4038 which were isolated from Astragalus cruciatus and Argyrolobium uniflorum growing on the same Tunisian soils (Zakhia et al, 2004;Mahdhi et al, 2008). So, it would now be interesting to test the cross-nodulation capacity of our new isolates on A. cruciatus and A. uniflorum legumes.It has been previously reported that A. corrugatus is nodulated by strains belonging to the genera Rhizobium, Sinorhizobium, Brdyrhizobium, Mesorhizobium, Agrobacterium and Phyllobacterium (Wei et al, 2003;Gao et al, 2004;Zakhia et al, 2004;Mantelin et al, 2006;Guerrouj et al, 2013;Zheng et al, 2013;Gnat et al, 2014). Our results thus confirm the previous studies showing the large diversity of A. corrugatus rhizobia that belong to Rhizobium, Sinorhizobium, Mesorhizobium and Agrobacterium.…”
supporting
confidence: 92%
“…STM4038 which were isolated from Astragalus cruciatus and Argyrolobium uniflorum growing on the same Tunisian soils (Zakhia et al, 2004;Mahdhi et al, 2008). So, it would now be interesting to test the cross-nodulation capacity of our new isolates on A. cruciatus and A. uniflorum legumes.It has been previously reported that A. corrugatus is nodulated by strains belonging to the genera Rhizobium, Sinorhizobium, Brdyrhizobium, Mesorhizobium, Agrobacterium and Phyllobacterium (Wei et al, 2003;Gao et al, 2004;Zakhia et al, 2004;Mantelin et al, 2006;Guerrouj et al, 2013;Zheng et al, 2013;Gnat et al, 2014). Our results thus confirm the previous studies showing the large diversity of A. corrugatus rhizobia that belong to Rhizobium, Sinorhizobium, Mesorhizobium and Agrobacterium.…”
supporting
confidence: 92%
“…The studies conducted in Hawaii to examine serological relatedness of 25 strains of slow-growing Rhizobia japonicum by agglutination identified 6 somatic serogroups [143] [149] Raposeiras, and Marriel [150] in Brazil reported that SLA 2.2 native rhizobia strain and CIAT 899 commercial strains are competitive strain for bean inoculation in soils with low fertility and reduced rhizobia population. Gao and Yang [48] in China reported that strain 042B could form nodules and fix nitrogen to both alfalfa and soybeans with nodule occupancy ranging from 82% -90% while that of strain USDA110 ranged from 78% -46%. Bizarro and Giongo [151] in Brazil reported that 27/75 isolates from soybeans were similar to original strain with strong correlation obtained in their genetic variability.…”
Section: Estimation and Characterization Of Rhizobia Population Usingmentioning
confidence: 99%
“…However, rhizobia are thought to be present before the legumes for nodulation because Sino rhizobium-Bradyrhizobium split was reported about 500 Ma [48] [49]. Bacteria of the genus Bradyrhizobium, Rhizobium Sinorhizobium and others induce nitrogen-fixing nodules on the roots of legumes such as peas, beans, cow peas and soybeans [50].…”
Section: Legume-rhizobia Symbiosismentioning
confidence: 99%
“…The G+C content of genomic DNA of the type strain was 53.4 mol%. The value of genomic DNA G+C content in the validated species belonging to the genus Mesorhizobium that showed the highest 16S rRNA gene sequence similarity with the novel strain, is in the range of 59~65.1 mol% (Jarvis et al, 1997;Gao et al, 2004). The G+C content value of strain N8 T genomic DNA is relatively lower than the values for validated species of the genus Mesorhizobium.…”
mentioning
confidence: 67%